2018
DOI: 10.1002/aocs.12170
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin from Haematococcus pluvialis Microencapsulated by Spray Drying: Characterization and Antioxidant Activity

Abstract: Astaxanthin (AX) is an unstable functional food ingredient. A stable AX powder was developed and its characteristics (such as moisture content, bulk density, solubility, repose angle, and morphology) and antioxidant activity were evaluated. The microencapsulated AX powder was produced by spray drying using maltodextrin (MD)-gelatin and the parameters were optimized by response surface methodology. The results revealed that an optimal microencapsulation process has a ratio of MD to gelatin of 2.1:1, a ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…Besides acting as a carrier, microcapsules prepared by spray drying are known to improve the solubility of the bioactive compounds encapsulated. Similarly high water solubility was found by Zhao et al 26 for spray-dried gelatin-dextrose microcapsules encapsulating astaxanthin (96.2%) and by Venil et al 27 for spray-dried κ-carrageenan microcapsules containing a flexirubin-type pigment (91.6%). It should be noted that no extra-compound was added to the formulation to favour the crosslinking of iota-carrageenan, which could explain the high water solubility values of spray-dried microcapsules.…”
Section: Resultssupporting
confidence: 59%
“…Besides acting as a carrier, microcapsules prepared by spray drying are known to improve the solubility of the bioactive compounds encapsulated. Similarly high water solubility was found by Zhao et al 26 for spray-dried gelatin-dextrose microcapsules encapsulating astaxanthin (96.2%) and by Venil et al 27 for spray-dried κ-carrageenan microcapsules containing a flexirubin-type pigment (91.6%). It should be noted that no extra-compound was added to the formulation to favour the crosslinking of iota-carrageenan, which could explain the high water solubility values of spray-dried microcapsules.…”
Section: Resultssupporting
confidence: 59%
“…The need for specific release conditions or specific release rates is another factor affecting the selection of the encapsulation method and the wall material. Drug release from a polymer matrix can be categorized in three main processes or systems [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]: (1) diffusion from the non-degraded polymer (diffusion-controlled system); (2) enhanced drug diffusion due to polymer swelling (swelling-controlled system); (3) release by polymer degradation and erosion (erosion-controlled system). Generally speaking, the release velocity will follow the order 3 > 2 > 1.…”
Section: Insights Into the Selection Of Encapsulation Methods And Wmentioning
confidence: 99%
“…The main drawbacks of this ingredient are that pure astaxanthin needs to be used for proper inclusion complex formation and that the astaxanthin:β-cyclodextrin optimum ratio to form the complexes is very high (1:200), thus hindering its applications in the food sector. On the other side, it is spray-drying, which is a widespread cost-effective drying method in food industries that have been assayed for the encapsulation of astaxanthin extracts from both microalgae or shrimp by-products with good results at improving functionality [ 57 , 58 , 60 , 78 , 79 , 92 , 93 , 94 , 95 ]. This process also has the advantage, as compared with cyclodextrin inclusion complexation, of upgrading the whole ingredient, avoiding any additional separation steps.…”
Section: Encapsulation Technologies To Improve the Technological Fmentioning
confidence: 99%
“…Studies on rats showed an increase in the content of antioxidant enzymes, such as catalase, superoxide dismutase and glutathione peroxidase after cyclic dosing of astaxanthin [ 116 , 124 ]. Astaxanthin has the status of pure antioxidant, which means that it does not have any pro-oxidative properties [ 129 ]. The main obstacle to the industrial use of astaxanthin is its low chemical stability during storage.…”
Section: Astaxanthin In the Human And Animal Dietmentioning
confidence: 99%
“…The microcapsules showed good spherical shapes with a smooth surface and good solubility. The use of cheap carriers makes the process economically profitable [ 129 ].…”
Section: Astaxanthin In the Human And Animal Dietmentioning
confidence: 99%